If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 0 = -7 Reorder the terms: 0 + -4x = -7 Remove the zero: -4x = -7 Solving -4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-4'. x = 1.75 Simplifying x = 1.75
| 64a^2b-16a^3+18a^2b-9=0 | | 4x-2(x-9)=26 | | X-24=42 | | -4(6)+y=-7 | | 8(12+a)= | | -4x+4(-x-14)=-144 | | 2t^2/16t | | -3(5w-4)+9w=2(w+8) | | 5(3y-2)=(4y+4)+2y | | -4(5)+y=-7 | | -3(-7u+5)-5u=6(u-2)-5 | | 21=.5h(6+1) | | 6*-y=3 | | 4a+3a=-20 | | -2(y+1)=9y-2+2(2y+6) | | Y-x=-15 | | -39-26+x= | | 6x-6(-x+18)=12 | | 5(-2x+1)=35 | | .5(8-c)=7.5 | | 6y+6z=-1 | | .7(x-2)=3 | | 65=98 | | 4x+20y=3 | | X=1/180 | | y=f(x)+3 | | 5-3x=25 | | -2y-3(4-2Y)=2(y-3)+6 | | 2y+x(2-y)=9 | | 221=(4+x)(x) | | 7+2(2y-2)=-3(3y-6)+4y | | x=(-13) |